The U.S. energy diplomacy challenges in the condition of world energy markets transformation (South Caucasus vector) - Davtyan, Vahe; Khachikyan, Silva (YSU Journal of International Affairs, 2022)
The article considers the key aspects of the US energy diplomacy in the context of the transformation of the global energy market at the present stage. The main strategic documents of the U.S., affecting the problems of energy security and energy strategy, are studied. The features of the concepts of "energy dominance" (Trump) and "energy independence" (Nixon) are presented from the point of view of their implementation in the context of modern political and economic challenges. The structure of the U.S. energy balance is considered, which made it possible to determine the level of dependence on external supplies of hydrocarbon raw materials, especially oil. The priorities of the U.S. in the hydrocarbon market (both natural gas and oil) and renewable energy are studied through the prism of the climate agenda (in particular, the 2015 Paris agreement). Special attention is paid to the issues of liquefied natural gas (LNG) export from the U.S., especially towards European markets. The key risks and challenges of US energy diplomacy in the context of the conflict in Ukraine as well as geopolitical confrontation with Russia are identified. The US energy strategy in the South Caucasus is considered. The main features of the U.S. energy cooperation with Armenia, Georgia and Azerbaijan in the context of geopolitical challenges are revealed.
Keywords: United States; energy; diplomacy; security; climate change; South Caucasus